Mindfulness-based cognitive therapy improves insomnia symptoms in individuals with recurrent depression: secondary analyses from a randomized controlled trial - Evanger, Linn Nyjordet; Flo-Groeneboom, Elisabeth; Sørensen, Lin; Schanche, Elisabeth (Frontiers in Psychiatry, 2024)
Recurrent depressive disorder is a highly prevalent and often disabling disorder. Research suggests that insomnia increases the risk of relapse and recurrence of depression. Mindfulness-based cognitive therapy (MBCT) is currently the recommended first-line option for recurrent depression, according to the UK National Institute of Health and Clinical Excellence; however, only two randomized controlled trials have previously investigated whether MBCT affects insomnia. The present secondary study demonstrated that MBCT improved several insomnia parameters among remitted adult patients with at least three prior episodes of depression. To our knowledge, this is the largest controlled studies on the effects of MBCT on insomnia symptoms conducted to date. Results may enhance the understanding of how insomnia is manifested among recurrently depressed individuals specifically, as well as of how MBCT affects insomnia.